2018
DOI: 10.22190/fumi1802217s
|View full text |Cite
|
Sign up to set email alerts
|

SOME TYPES OF Η-Ricci SOLITONS ON LORENTZIAN PARA-SASAKIAN MANIFOLDS

Abstract: In this paper we study some types of  η-Ricci solitons on Lorentzianpara-Sasakian manifolds and we give an example of  η-Ricci solitons on 3-dimensional Lorentzian para-Sasakian manifold. We obtain the conditions of  η-Ricci soliton on ϕ-conformally flat, ϕ-conharmonically flat and ϕ-projectivelyflat Lorentzian para-Sasakian manifolds, the existence of η-Ricci solitons implies that (M,g) is  η-Einstein manifold. In these cases there is no Ricci solitonon M with the potential vector field

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…is called φ-conharmonically flat [13], where H is the conharmonic curvature tensor of M n . Let (M, φ, ξ, η, g) be a (2n+1) dimensional φ-conharmonically flat Sasakian manifold.…”
Section: Curvature Properties On Sasakian Manifold Satisfying * -Conf...mentioning
confidence: 99%
“…is called φ-conharmonically flat [13], where H is the conharmonic curvature tensor of M n . Let (M, φ, ξ, η, g) be a (2n+1) dimensional φ-conharmonically flat Sasakian manifold.…”
Section: Curvature Properties On Sasakian Manifold Satisfying * -Conf...mentioning
confidence: 99%
“…Since the introduction of Ricci soliton and Yamabe soliton, many authors ( [21], [22], [9], [6], [8], [18]) have studied these solitons on contact manifolds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently an η-Ricci soliton has been studied by several authors such as [3,5,16,20,8,4] and they found many interesting geometric properties.…”
Section: Introductionmentioning
confidence: 99%